Analogical Reasoning Ability of Mathematics Education Students at Six State Islamic Universities (UIN) in Indonesia - Maifalinda Fatra; Lilis Marina Angraini (USN Kolaka, 2020)
Mathematical abilities that students must possess at the level of primary and secondary education must also be possessed by a student of teacher candidates who will teach mathematics. One of the abilities is an analogical reasoning ability. The main objectives of this research are: 1) To describe and analyze analogical reasoning ability of students of mathematics education at the State Islamic Universities (UIN) in Indonesia, 2) To know the differences of analogical reasoning abilities of students of mathematics education at several State Islamic Universities (UIN) in Indonesia. The study was conducted at 6 UINs in Indonesia with a sample of 203 5th semester students using a survey method. This study's results indicate: 1) Analogical reasoning ability in Mathematics Education students consisting of 6 UINs in Indonesia can be seen from the average value in each sample. The acquisition of the average value of UIN Syarif Hidayatullah Jakarta students' analogical reasoning ability is the highest compared to the other 5 UINs with an average mathematical reasoning ability value of 65. 2. There is a difference in mathematics education students' analogical reasoning ability at the State Islamic Universities (UIN) in Indonesia.